Teachers' Autonomy-Relevant Practices within an Inquiry-Based Science Curricular Context: Extending the Range of Academically Significant Autonomy-Supportive Practices. Issue 7 (July 2014) - Rogat, Toni Kempler; Witham, Shelly Anne; Chinn, Clark
Background: Research in traditional classrooms and laboratories has indicated that autonomy support by teachers is infrequent and focused on the narrow provision of choice. One explanation for the limited autonomy support in classrooms is that typical school resources and tasks limit the availability of experiences that are interesting, relevant, with meaningful choice. Accordingly, it is critical to extend observation to contexts that enhance the likelihood of detecting significant autonomy support. In this way, it will be possible to (a) determine whether existing conceptualizations map onto behaviors in real classrooms and (b) enrich our understanding of the variety of ways in which teachers provide autonomy when the curriculum is designed not to constrain it but to expand it. Objective: In the current study, we extend and develop conceptualizations of autonomy support based on our observations within an inquiry context that offers a broad range of forms of autonomy, thus gaining access to a more elaborated understanding of how real teachers offer this support. We elaborate on and richly describe how classroom teachers support autonomy in ways that extend the range of current conceptualizations, with implications for lending validity to the construct and providing concrete description for practitioners. Research Design: Qualitative analyses were conducted based on videotaped observations of four 7th-grade science teachers, each enacting five inquiry-based science lessons designed to encourage scientific reasoning. We developed a coding protocol grounded in theoretical conceptualizations organized around five autonomy-support dimensions (i.e., procedural and organizational support, rationale and relevance, responsiveness, feedback, cognitive autonomy support). We were exploratory in our use of content analysis in ways that evolved our initial codes, given our aim to enrich and extend available characterizations of autonomy-supportive practice to incorporate new conceptualizations of higher quality practice. Conclusions: Observed enactments provide support for modifying our conceptualizations of the upper end points of autonomy support to include more academically significant forms as well as for making new distinctions in forms of autonomy support. This high quality and multifaceted enactment was possible because practice was embedded within an inquiry-based curriculum context that expanded opportunities for student agency. Implications for supporting educational leaders in facilitating teacher practice using this thick description and set of exemplars are discussed.